Answer:
See explanations below
Explanation:
Given the function
f(x) = 3x+12
Let y = f(x)
y = 3x+12
Replace y with x
x = 3y+12
Make y the subject
3y = x-12
y = (x-12)/3
Hence the required inverse is!
g(x) = (x-12)/3
b) To show that the functions are inverses, we must show that f(g(x)) = g(f(x))
f(g(x)) = f((x-12)/3)
Replace x in f(x) with x-12/3
f(g(x)) = 3(x-12)/3 +12
f(g(x)) = x-12+12
f(g(x)) = x
Similarly for g(f(x))
g(f(x)) = g(3x+12)
g(f(x)) = (3x+12-12)/3
g(f(x)) = 3x/3
g(f(x)) = x
Since f(g(x)) = g(f(x)) = x, hence they are inverses of each other
c) Given f(g(x)) = x
f(g(–2)) = -2
The domain is the input variable of the function. Hence the domain is -2